Experimental Investigations of Vibrations Induced by Cross-flow in a Bundle of Tubes through Wind Tunnel - Hayat, N.; Rashid, M. A.; Bhutta, M.M. A. (The Nucleus, 2019)
<span style="font-size: 10.0pt; mso-bidi-font-size: 8.0pt; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Experimental investigations of vibrations induced by cross-flow in a tube bundle have been carried out in this research work. Vibration behavior of one tube in a bundle of tubes has been examined by placing it to a subsonic wind tunnel having cross-flowing air. The tube bundle consists of seven PVC tubes arranged in a rotated triangular configuration. The target tube is fitted with strain gauges to measure the amplitude response in flow and lateral directions for each value of the upstream velocity. Results show that surrounding tubes cause upstream flow which causes turbulence. Because of that, amplitude of vibrations of the tube under consideration remains small in a low range of velocity. With an increase in flow velocity beyond a threshold-velocity, vibrations amplitudes increase significantly which indicates the start of unstable fluid elasticity. Hence, the occurrence of unstable fluid elasticity can be prevented by either keeping the cross-flow velocities below the critical velocity or by controlling the damping ratio of the tubes